Potential risk of paraffin wax-related problems in malaysian oil fields - Kelechukwu, Ekeh Modesty; Md. Yassin, Abu Azam (Penerbit UTM Press, 2008)
Paraffin wax deposition in production system constitutes a critical concern to crude exploration and production operations. The unwanted effect of wax deposition can cause serious production impairment and other associated hazardous risk. While its curative approaches and production losses adds to colossal economic sabotage to the petroleum industry. The strategy employed in this study was to use temperature and fluid characterization analysis of Malaysian crude to predict the potential for paraffin wax related problems in Malaysian oilfields. This approach defined the oilfields with probably high risk of wax deposition potential amongst Malaysian crude. The synopsis of this paper proved that some Malaysian oilfield presents a potentially serious problem.